The Analysis of Factors Affecting Interest in Fertile Age Women in Performing Early Detection of Cervical Cancer at Community Health Center Kubutambahan I Buleleng Regency-Bali - Putu Indah Sintya Dewi (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
One effort to prevent cervical cancer is to do early detection of cervical cancer, but often this is ignored because of lack of knowledge, interest and information on early detection of cervical cancer. This study aimed to analyze the influence of the characteristics of FAW, attitudes and subjective norms of FAW on the interest of early detection of cervical cancer at Community Health Center Kubutambahan I. This type of research was an observational analytic cross-sectional design study. The population in this study FAW who visited at Community Health Center Kubutambahan I with a sample of 104 FAW sampling technique that was simple random sampling. Bivariate data analysis used chi square statistical tests and multivariate analysis used logistic regression. The results of this study that there is a knowledge factor influencing interest with a p-value of 0.023 <0.05, attitude factor influencing interest with a p-value of 0.023 <0.05, there are subjective norm factors influencing FAW interest in detecting cervical cancer with p -value 0.016 <0.05 and educational and occupational factors do not affect FAW interest in detecting cervical cancer with p-value> 0.05. The conclusion of this study did not significantly influence education and employment factors with a p value> 0.05. While knowledge, attitudes and subjective norms are factors that influence significantly with a p value <0.05. The dominant factor influencing FAW's interest in early detection of cervical cancer is subjective norm